RESOLUSI KONFLIK UMAT AGAMA BAHA’I DENGAN MUSLIM: STUDI KASUS DI PATI JAWA TENGAH - Moh Rosyid (Harmoni, 2019)
This research was conducted in 2018 among Baha’i community in Cebolek Kidul, Margoyoso, Pati, Central Java. The purpose of this study is to describe conflict resolution between Baha’i community and their Muslim neighbors. Data were gathered through interview, documentation, observation and focus group discussion. There are 9 (nine) families of Baha’i consisting of 27 people. In their village, some Muslims were accused Baha’i people as deviants. Thus Baha’i people were not allowed to be buried in the same cemetery as Muslims, in some cases Baha’i people also do not receive the same service in administrative matters from the village officers as their Muslims fellows such as do not receive religious education at formal school, do not have marriage certificate since their marriage is not acknowledged by the government. After the Reformation, Baha’i people struggle to gain public attentions in several ways: 1) distributing information on Baha’i through public meetings; 2) initiating non-formal religious class for Baha’i people and people of other religions; 3) inviting neighbors and friends during Baha’i religious celebration.